Human Monkeypox Outbreak Caused by Novel Virus Belonging to Congo Basin Clade, Sudan, 2005 - Pierre Formenty; Mohammed O. Muntasir; Inger K. Damon; Vipul Chowdhary; Martin L. Opoka; Charlotte Monimart; Elmangory M. Mutasim; Jean-Claude Manuguerra; Whitni B. Davidson; Kevin L. Karem; Jeanne Cabeza; Sharlenna Wang; et al. (Emerging Infectious Diseases, 2010)
To determine the outbreak source of monkeypox virus (MPXV) infections in Unity State, Sudan, in November 2005, we conducted a retrospective investigation. MPXV was identified in a sub-Sahelian savannah environment. Three case notification categories were used: suspected, probable, and confirmed. Molecular, virologic, and serologic assays were used to test blood specimens, vesicular swabs, and crust specimens obtained from symptomatic and recovering persons. Ten laboratory-confirmed cases and 9 probable cases of MPXV were reported during September–December 2005; no deaths occurred. Human-to-human transmission up to 5 generations was described. Our investigation could not fully determine the source of the outbreak. Preliminary data indicate that the MPXV strain isolated during this outbreak was a novel virus belonging to the Congo Basin clade. Our results indicate that MPXV should be considered endemic to the wetland areas of Unity State. This finding will enhance understanding of the ecologic niche for this virus.